Do I need a new name for the Librarian? - Chacón Alvarado, Lucía (1998)
There is no doubt that Library Schools are preparing students to face the imminent changes affecting the library profession through a solid training that allows them to compete in a technocratized environment with absolute confidence and security, but have we set about reflecting on the common opinion of people about the library profession and about librarians?